Enhancing anomaly detection in plant disease recognition with knowledge ensemble - Dong, Jiuqing; Zhou, Heng; Fuentes, Alvaro; Yoon, Sook; Park, Dong Sun (Frontiers in Plant Science, 2025)
Plant diseases pose a significant threat to agriculture, impacting food security and public health. Most existing plant disease recognition methods operate within closed-set settings, where disease categories are fixed during training, making them ineffective against novel diseases. This study extends plant disease recognition to an open-set scenario, enabling the identification of both known and unknown classes for real-world applicability. We first benchmark the anomaly detection performance of three major visual frameworks—convolutional neural networks (CNNs), vision transformers (ViTs), and vision-language models (VLMs)—under varying fine-tuning strategies. To address the limitations of individual models, we propose a knowledge-ensemble-based method that integrates the general knowledge from pre-trained models with domain-specific knowledge from fine-tuned models in the logit and feature spaces. Our method significantly improves over existing baselines. For example, on vision-language models with 16-shot per class, our approach reduces the FPR@TPR95 from 43.88% to 7.05%; in the all-shot setting, it reduces the FPR@TPR95 from 15.38% to 0.71%. Extensive experiments confirm the robustness and generalizability of our approach across diverse model architectures and training paradigms. We will release the code soon at https://github.com/JiuqingDong/Enhancing_Anomaly_Detection.